2006
DOI: 10.1021/jf052068+
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of trans-2-Hexenal in Response to Wounding in Strawberry Fruit

Abstract: Wounded strawberry fruit produces a diverse group of volatile compounds including aldehydes, alcohols, and esters derived from the lipoxygenase (LOX) and hydroperoxide lyase (HPL) pathways. Because the wound volatiles may play an important role in plant-fungal interaction, the goal of this study was to develop a greater understanding about the biosynthesis of the major wound volatile, trans-2-hexenal (t-2-H), produced by strawberry fruit upon wounding. To that end, composition and quantity of total and free fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 54 publications
4
40
1
Order By: Relevance
“…The cutting process resulted in tissue disruption and membrane breakdown leading to the release of hydrolytic enzymes. Enzymatic degradation of cellulose, hemicellulose and pectin led to texture losses during storage (Myung, Hamilton-Kemp, & Archbold, 2006). This effect, being pronounced in freshly cut samples in the present study, was not reduced by the potassium metabisulfite dip or its combination with osmotic dehydration.…”
Section: Texture Analysiscontrasting
confidence: 46%
“…The cutting process resulted in tissue disruption and membrane breakdown leading to the release of hydrolytic enzymes. Enzymatic degradation of cellulose, hemicellulose and pectin led to texture losses during storage (Myung, Hamilton-Kemp, & Archbold, 2006). This effect, being pronounced in freshly cut samples in the present study, was not reduced by the potassium metabisulfite dip or its combination with osmotic dehydration.…”
Section: Texture Analysiscontrasting
confidence: 46%
“…S6A). This expression might contribute to producing (E)-2-hexenal as an antifungus volatile as in strawberry (37). In potato, higher expression of StHI1 and StHI2 was observed in sprouts (supplemental Fig.…”
Section: (Z)-3:(e)-2-hexenal Isomerases Producing the Leaf Aldehydementioning
confidence: 93%
“…Studies have shown a rapid increase in the lipoxygenase VvLOXC and -O transcripts in B. cinerea infected berries. These enzymes are responsible for the release of (E)-2-hexenal (HamiltonKemp, Archbold, Collins, & Yu, 2003;Hatanaka, 1993;Myung, Hamilton-Kemp, & Archbold, 2006) and other reactive aldehydes such as hexanal and nonenal (Mueller, 2004). These compounds are toxic to the pathogen and can become toxic to the plant itself at a critical level (Hamilton-Kemp et al, 2003;Hatanaka, 1993;Myung et al, 2006).…”
Section: Precursors Of Volatile Thiolsmentioning
confidence: 99%